The Structure of Reflection Competency During Social Work Students’ Practices - Bubnys, Remigijus (Socialinė teorija, empirija, politika ir praktika, 2014)
SummaryThe article discloses structural components of reflection competency, which distinguished themselves during social work students’ professional practice. The results of factor analysis allow stating that the structure of social work students’ reflection competency encompasses reflection on learning and for learning, self-reflection and reflection in learning as well as abilities of critical thinking and problem solving, experiential analysis and learning from experience. It was found during the research that during the practice social work students successfully applied three abilities of reflection on experience competency: reflection in learning, on learning and for learning. Students’ least mastered skills making up the self-reflection ability are recognition and management of lived emotions, critical thinking and problem solving.Key words: social work practice, reflection competency, reflection abilities, student, higher education institution